Impaired gamma delta T cell‐derived IL‐17A and inflammasome activation during early respiratory syncytial virus infection in infants. Issue 2 (30th September 2014) - Huang, Huaqiong; Saravia, Jordy; You, Dahui; Shaw, Aaron J; Cormier, Stephania A
Abstract : Respiratory syncytial virus (RSV) infection remains a significant global health burden disproportionately affecting infants and leading to long‐term lung disease. Interleukin (IL)‐17A has been shown to be involved in regulating viral and allergic lung inflammatory responses, which has led to a more recent interest in its role in RSV infection. Using a neonatal mouse model of RSV, we demonstrate that neonates fail to develop IL‐17A responses compared with adult mice; the main immediate IL‐17A contributor in adults were γδ T cells. Antibody neutralization of IL‐17A in adult mice caused increased lung inflammation and airway mucus from RSV, whereas exogenous IL‐17A administration to RSV‐infected neonates caused decreased inflammation but no change in airway mucus. We also observed a lack of pro‐inflammatory cytokine production (IL‐1β, IL‐6) from infected neonates. Using human cord blood mononuclear cells (CBMCs) and adult peripheral blood mononuclear cells (PBMCs), we compared inflammasome activation by direct retinoic acid‐inducible gene I agonism; CBMCs failed to induce pro‐inflammatory cytokines or IL‐17A + γδ T cells compared with PBMCs. Our results indicate that RSV disease severity is in part mediated by a lack of inflammasome activation and IL‐17A production in neonates.